Pengaruh Inovasi Hijau dan Efisiensi Lingkungan terhadap Keunggulan Kompetitif Perusahaan - Ningsi, Wanny Putri; Haq, Aqamal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of green innovation and eco-efficiency on the competitive advantage of companies. The research sample was selected from companies operating in the energy, industrial, tobacco sub-sector, and nondurable household product industries that are listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2021. A purposive sampling technique was employed, resulting in 109 companies that met the criteria from a total of 327 observations. Data analysis was conducted using multiple linear regression to test the effect of the independent variables on the dependent variable.In this study, green innovation and eco-efficiency are treated as independent variables, measured using content analysis based on annual and sustainability reports. Meanwhile, competitive advantage serves as the dependent variable and is measured using the Return on Invested Capital (ROIC) ratio. The findings reveal that green innovation has a positive impact on a company's competitive advantage. Similarly, eco-efficiency also shows a favorable influence. These results suggest that implementing sustainable strategies such as green innovation and eco-efficiency plays a vital role in enhancing company competitiveness, especially amid growing industrial competition and increasing demands for environmental responsibility.